2020
DOI: 10.3389/fphar.2020.00117
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Chronic Plaque Psoriasis and Its Intersection With Cardio-Metabolic Comorbidities

Abstract: Psoriasis is a chronic, systemic immune-mediated disease characterized by development of erythematous, indurated, scaly, pruritic plaques on the skin. Psoriasis is frequently associated to comorbidities, including psoriatic arthritis, cardiovascular diseases, diabetes mellitus, obesity, non-alcoholic fatty liver disease, and inflammatory bowel diseases. In this review, we discuss the pathophysiological relationship between psoriasis and cardio-metabolic comorbidities and the importance of therapeutic strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 100 publications
2
96
0
3
Order By: Relevance
“…In the course of Ps, increased triglycerides, LDL cholesterol and decreased HDL cholesterol values are the most frequently observed lipid disturbances [1,2]. In our study, the levels of total CHOL and TG as well as CHOL/HDL and TG/HDL ratios were significantly higher in Ps patients than in HVs, while LDL-CHOL did not differ between both groups.…”
Section: Discussionsupporting
confidence: 46%
“…In the course of Ps, increased triglycerides, LDL cholesterol and decreased HDL cholesterol values are the most frequently observed lipid disturbances [1,2]. In our study, the levels of total CHOL and TG as well as CHOL/HDL and TG/HDL ratios were significantly higher in Ps patients than in HVs, while LDL-CHOL did not differ between both groups.…”
Section: Discussionsupporting
confidence: 46%
“…This association could be due to shared genetic factors and chronic inflammatory pathways between psoriasis and MetS. 17 Autophagy study has been growing in skin diseases including psoriasis. 18 In the same context, autophagy has a growing contribution to MetS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic inflammatory skin disorder resulting from genetic and environmental factors, in which disturbances of innate and adaptive cutaneous immune responses lead to uncontrolled keratinocyte proliferation and dysfunctional differentiation [ 29 ]. In psoriasis, IL-17A-producing CD4 + and CD8 + T cells play a key pathogenic role.…”
Section: Ll-37 In Autoimmune Diseasesmentioning
confidence: 99%
“…In the early events of psoriasis development, keratinocytes overproduce several innate immunity mediators, including IL-1 cytokines, chemokines, and AMPs—in particular LL-37, HBD-2, and psoriasin. These are involved in the activation and skin recruitment of innate immunity cells, such as plasmacytoid dendritic cells (pDC), neutrophils, and macrophages and mast cells ( Figure 1 ) [ 27 , 29 ]. In 2007, Lande et al demonstrated that LL-37 is the principal trigger of the pathogenic innate immune responses in psoriatic skin, providing the first link between an antimicrobial defense system and the pathogenesis of psoriasis [ 19 ].…”
Section: Ll-37 In Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation